Carbonate‐Hydroxide Induced Metal‐Organic Framework Transformation Strategy for Honeycomb‐Like NiCoP Nanoplates to Drive Enhanced pH‐Universal Hydrogen Evolution. Issue 8 (1st July 2022) - Zhang, Lin; Ye, Fei; Wu, Zeyi; Jiang, Le; Liu, Qiang; Pang, Ruilvjing; Liu, Yang; Hu, Linfeng
Abstract: Developing a low‐cost, pH‐universal electrocatalyst is desirable for electrochemical water splitting but remains a challenge. NiCoP is a promising non‐noble hydrogen‐evolving electrocatalyst due to its high intrinsic electrical conductivity, fast mass transfer effects, and tunable electronic structure. Nevertheless, its hydrogen evolution reaction (HER) activity in full pH‐range has been rarely developed. Herein, a Ni–Co carbonate‐hydroxide induced metal‐organic framework transformation strategy is proposed to in situ grow porous, honeycomb‐like NiCoP nanoplates on Ni foam for high‐performance, pH‐universal hydrogen evolution reaction. The resultant NiCoP catalyst exhibits a highly 2D nanoporous network in which 20–50 nm, well‐crystalline nanoparticles are interconnected with each other closely, and delivers versatile HER electroactivity with η10 of 98, 105, and 97 mV in 1 m KOH, 0.5 m H2 SO4, and 1 m phosphate buffer solution electrolytes, respectively. This overpotential remarkably surpasses the one of commercial Pt/Cs in both neutral and alkaline media at a large current density (> 100 mA cm −2 ). The corresponding full water‐splitting electrolyzer constructed from the 2D porous NiCoP cathode requires only a cell voltage of 1.43 V at 10 mA cm −2, superior to most recently reported electrocatalysts. This work may open up a new avenue on the rational design of nonprecious, pH‐universal electrocatalyst. Abstract : A carbonates‐hydroxide induced metal‐organic framework transformation strategy was developed to in situ grow honeycomb‐like 2D NiCoP nanoplates on Ni foam as a high‐performance, pH‐universal hydrogen evolution reaction catalyst. The corresponding full water‐splitting electrolyzer constructed from the 2D porous NiCoP cathode requires only a cell voltage of 1.43 V at 10 mA cm −2 owing to a low overpotential of 202 mV.